Research for development approaches in mixed crop-livestock systems of the Ethiopian highlands - Mekonnen, Kindu; Thorne, Peter; Gebreyes, Million; Hammond, James; Bezabih, Melkamu; Kemal, Seid Ahmed; Tamene, Lulseged; Agegnehu, Getachew; Yahaya, Rabe; Gebrekirstos, Aster; Thai, Minh; Sharma, Kalpana; et al. (Frontiers in Sustainable Food Systems, 2023)
This paper presents processes and success stories that emerged from the Research for Development project of Africa RISING in the Ethiopia Highlands. The project has tested a combination of participatory tools at multiple levels, with systems thinking and concern for sustainable and diversified livelihoods. Bottom-up approaches guided the selection of technological interventions that can address community priority farming system challenges, leading to higher uptake levels and increased impact. Key to this was joint learning, appropriate selection of technologies, and the creation of an enabling environment such as forming farmers' research groups, establishing innovation platforms, and capacity development concerning institutional and technical innovations. The paper concludes by identifying key lessons that focus more on matching innovations with community needs and geographies, systems orientation/integration of innovations, stepwise approaches to enhance the adoption of innovations, documentation of farmers' capacity of modifying innovations, building successful partnerships and facilitation of wider scaling of innovations for future implementation of agricultural research for development projects.